Two new species from the Ile des Pins (New Caledonia), and a not so new species from Grande Terre (New Caledonia) - Meve, Ulrich; Gâteblé, Gildas; Liede-Schumann, Sigrid (Phytotaxa, 2018)
Two New Caledonian endemics of Apocynaceae-Asclepiadoideae, predominantly natives of the Ile des Pins, an island south of New Caledonia known for its high microendemism, are here described as new to science. One new species, Heterostemma bicanthaceum (Ceropegieae), is related to H. acuminatum Decne. but differs remarkably in a number of floral characters such as a raised central corolla tube, and a dull purple-brown and wrinkled corona with expanded lateral appendages forming coronal rail-like structures. The other species described and illustrated, Marsdenia kuniensis (Marsdenieae), is sister to Marsdenia dognyensis from the Grande Terre. Its fleshy whitish to rose corolla with the tube closely encircling the corona as well as protruding and deltoid corona lobes broader than long distinguish the new species. These two species are restricted to calcareous forests and a preliminary IUCN red list assessment is proposed. Additionally, the name Marsdenia neomicrostoma is proposed for a species whose members have hitherto mostly been listed under the name Marsdenia microstoma, a name that has to be considered as nomen dubium after its type has been lost. The species is a typical element of ultramafic soil vegetation, and therefore widespread on Grande Terre but missing on the Ile des Pins.